Preface. Issue 1 (2nd January 2022) - Parkes, Stephen; Ferrari, Ed
Abstract : Cities and regions continue to grapple with a multitude of social, environmental and economic challenges that impact their residents. These challenges have been further compounded by the climate crisis (and the need to deliver on net zero commitments) and the Covid-19 pandemic, which has stretched local government resources even further whilst posing fundamental questions about the role of cities within their regions.